The future of architectural education in Malaysia: introducing a new theory of studiogogy using SOLE module - Mohd Noor, Mohd Zairul (Pertubuhan Akitek Malaysia, 2019)
At the moment, the architecture profession in the construction industry is facing a rapid change relating to technology and knowledge information. New ways of thinking about education (and about architectural education in particular) have suggested new approaches which are in line with the rapid advances in technology. Researchers are concerned on the current architectural graduates who lack the collaboration and teamwork skills besides the computer skills as their essential abilities ((BecerikGerber, Gerber, & Ku, 2011; Johnson & Gunderson, 2010). Educators should be ready to integrate technology into their innovative teaching and learning to make their lesson more effective. The lack of adequate workforce equipped with the latest technology is hampering the industry to move forward (Becerik-Gerber et al., 2011). Furthermore, innovation and active learning are the near future especially towards the architecture field of study (Khalifa, 2017). Also, Nabih, (2010) argued that lecture-based education could lead to the disparity in understanding the practical problems in reality. In the twenty-first century, architectural graduates must have the skills to deal with everchanging technology that requires quick solutions skills.